Primary skeletal muscle myoblasts from chronic heart failure patients exhibit loss of anti-inflammatory and proliferative activity. Issue 1 (December 2016) - Sente, Tahnee; Van Berendoncks, An; Jonckheere, An; Rodenburg, Richard; Lauwers, Patrick; Van Hoof, Viviane; Wouters, An; Lardon, Filip; Hoymans, Vicky; Vrints, Christiaan
Abstract Background Peripheral skeletal muscle wasting is a common finding with adverse effects in chronic heart failure (HF). Whereas its clinical relevance is beyond doubt, the underlying pathophysiological mechanisms are not yet fully elucidated. We aimed to introduce and characterize the primary culture of skeletal muscle cells from individual HF patients as a supportive model to study this muscle loss. Methods and results Primary myoblast and myotubes cultures were successfully propagated from them. vastus lateralis of 6 HF patients with reduced ejection fraction (HFrEF; LVEF <45 %) and 6 age and gender-matched healthy donors. HFrEF cultures were not different from healthy donors in terms of morphology, such as myoblast size, shape and actin microfilament. Differentiation and fusion indexes were identical between groups. Myoblast proliferation in logarithmic growth phase, however, was attenuated in the HFrEF group (p  = 0.032). In addition, HFrEF myoblasts are characterized by a reduced TNFR2 expression and IL-6 secretion (p  = 0.017 andp  = 0.016; respectively). Conclusion Biopsy derived primary skeletal muscle myoblasts of HFrEF patients produce similar morphological and myogenic differentiation responses as myoblasts of healthy donors, though demonstrate loss of anti-inflammatory and proliferative activity.